Strategy of solution process precursors for phase change memory. (15th January 2020) - Hwang, Jeong Min; Lee, Ji Hun; Kim, Hyo-Suk; Park, Chan Woo; Yoo, Dagyum; Park, Bo Keun; Kim, Chang Gyoun; Chung, Taek-Mo
Graphical abstract: Series of germanium and antimony precursors with varying α −carbon substituent group were synthesized. Prepared substances were further converted into GeTe or Sb2 Te3 by thermal reaction to elucidate the size and electronic effects of α −carbon substituent suggesting that less bulky group leads to better conversion of desired complexes. Abstract: In this study, the relationship between the steric hindrance of the alpha carbon substituent group of aminoalkoxy ligand and formation of germanium telluride (GeTe) and antimony telluride (Sb2 Te3 ) was elucidated. A series of germanium and antimony precursors was prepared using aminoalkoxide-type bidentate ligands of different sizes such as dmampH, dmapH and dmaeH. These precursor materials were further treated with bis (trimethylsilyl)telluride in hexadecane through thermal reaction and studied with powder X-ray diffraction (pXRD) to compare the formation of germanium telluride (GeTe) and antimony telluride (Sb2 Te3 ) alloys which are potential precursor materials for phase change random access memory devices. While the pXRD patterns of the thermal reaction materials of compounds 2 and 3 at 190 °C revealed a rhombohedral phase of GeTe and tellurium, compounds 5 and 6 at 190 °C showed a rhombohedral phase of Sb2 Te3 and tellurium at this temperature. These results suggested that the formation of chalcogenide alloys was more favorable when relatively less bulk ligand was used.